Implementation of Cloud Computing Technology for Vocational Higher Schools - Brandon Lee Judas (JR Education, 2022)
The development of technology is so very fast, it requires every individual and institution to follow it. Such as the use of cloud computing whose use is currently very broad. In the world of education, the use of cloud computing is very useful for teachers and students in terms of learning in the classroom and outside the classroom. The Gafe application stored in the cloud provides a large selection of office applications, chat and others. This system will try to be implemented in SMK 1 Sorong City which is currently still using the manual system. This system allows teachers and students to communicate with each other and interact with each other